Digital-Sensory Confluence in Hotel Brand Experience Formation: a Multi-Case Study on Grand Mercure Malang Mirama, the Alana Malang, and Bobobox Malang - Suprapto; Wening Patmi Rahay; Agus Hermawan (PT FORMOSA CENDEKIA GLOBAL, 2026)
Hotel competition is no longer determined solely by price and amenities, but rather by the brand's ability to build digital expectations that are consistent with guests' sensory experiences at service sites. This article aims to formulate a digital-sensory congruence model in the formation of hotel brand experiences using the context of three hotel brands in Malang City that have different positions: Grand Mercure Malang Mirama, The Alana Malang, and Bobobox Malang. The article was compiled as a conceptual study based on exploratory multi-case design through the synthesis of digital branding literature, online brand experience, sensory marketing, servicescape, and hospitality experience. The analysis yielded three conceptual findings. First, digital branding functions as a gateway to experience through websites, social media, online travel agents, online reviews, photos, videos, and applications. Second, sensory marketing is proof of the brand's promise through visual, auditory, olfactory, tactile, and gustatory stimuli that affect the perception of quality, comfort, trust, and memory of the experience. Third, congruence between digital appointments and actual sensory experiences is an important mechanism that bridges pre-stay expectations with post-stay satisfaction and advocacy. The contribution of this article is to offer a conceptual model, research proposition, as well as an empirical validation agenda for the development of a more measurable, ethical, and experience-oriented hotel branding strategy.